Management Of School Principles In Improving Teacher Performance In The Time Of Covid 19 At SMP Negeri 1 Kayangan - Jannah, Rauhun (Jurnal Ilmiah Mandala Education (JIME), 2022)
This study aimed to determine: 1) principal's management in improving teacher performance during the COVID-19 pandemic at SMP Negeri 1 Kayangan (State Junior High school 1 Kayangan), 2) teachers' motivation in enhancing their performance amid the pandemic, 3) supervision forms of teacher performance amid the pandemic. Thus, this qualitative descriptive gathered data through observation, interviews, and documentation techniques. The data were then analyzed qualitatively, employing the interactive method. Hence, the findings indicated that: 1) principal's management in increasing teacher performance during Covid-19 was carried out in several stages: a) planning, b) implementation, and c) supervision. 2) teachers' motivation to develop their performance amid the pandemic is reflected in two aspects: a) internal motivation because of hopes, goals, and desires to obtain maximum results. b) external motivation such as rewards in the form of incentives, praise, and rewards. 3) the principals conducted supervision forms of teacher performance during the pandemic by providing assessments to teachers by looking at pedagogic, personality, social, and professional aspects. Therefore, the principal's management in promoting teacher performance during COVID-19 can be carried out appropriately. Moreover, teachers' high motivation with rewards and punishments enhance their performance